AB0182 RECEPTOR ACTIVATOR OF NUCLEAR FACTOR-KAPPA B LIGAND (RANKL)/RANK AND OSTEOPROTEGERIN (OPG) PATHWAY ACTIVATION IN SJöGREN'S SYNDROME. (June 2019) - Skarlis, Charalampos; Palli, Eleni; Nezos, Adrianos; Mavragani, Clio
Abstract : Background: Primary Sjogren's syndrome (SS) is an autoimmune exocrinopathy characterized by chronic salivary and lacrimal glands dysfunction. Recent studies suggest that activation of the receptor activator of nuclear factor-kappa B ligand (RANKL)/RANK and osteoprotegerin (OPG) pathway is implicated in the development of autoimmunity. Objectives: The aim of this study is to investigate the contribution of RANK/RANKL/OPG pathway in primary SS pathogenesis. Methods: Sixty-six primary SS patients fulfilling the American/European criteria and 13 subjects with oral and/or ocular dryness without satisfying the aforementioned criteria (sicca controls, SC) and 11 healthy controls (HC) have been enrolled. RANKL and OPG serum levels were determined by ELISA in 29 SS patients and 11 HC. Total RNA was extracted from minor salivary glands biopsies (MSG) from 43 SS patients and 13 SC and RANKL mRNA expression was assessed by qRT-PCR. Protein expression of RANKL was determined by Western Blot and immunohistochemistry (IHC) in total protein extract and paraffin embedded tissue respectively, derived from MSG biopsies of 6 primary SS patients and 5 SC. Statistical analysis was performed with SPSS 24.0 package. Results: Increased serum levels (pg/ml) of RANKL (mean±SD=4.197±897.6vs mean±SD=144.8±290.2, p=0.013) and OPG (mean±SD=173.4±57.52, mean±SD=48.42±21.89, p=0.015) were detected in SS patients compared to HC. Higher RANKL at both mRNA and protein level by IHC were detected, in MSG derived from primary SS patients compared to SC. RANKL protein expression was significantly increased in MSG biopsies from primary SS patients compared to SC by Western Blot (mean±SD=2.468±1.896 vs mean±SD=0.5138±0.823, p=0.0335). Conclusion: Increased serum levels, mRNA and protein expression of RANKL in association with increased OPG titers in SS patients compared to controls, suggests that the activation of RANK/RANKL/OPG pathway contributes to SS pathogenesis. References: [1] Skopouli, F. N. & Moutsopoulos, H. M. Autoimmune epitheliitis: Sjögren's syndrome. Clin. Exp. Rheumatol. 12Suppl 11, S9-11 (1994). [2] Assmann, G. et al. Genetic variations in genes encoding RANK, RANKL, and OPG in rheumatoid arthritis: a case-control study. J. Rheumatol. 37, 900–904 (2010). Acknowledgement: Research Grant from the Greek Rheumatology Society and Professional Association of Rheumatologists Disclosure of Interests: None declared